2014
DOI: 10.1371/journal.pone.0101321
|View full text |Cite|
|
Sign up to set email alerts
|

Hesperidin Induces Paraptosis Like Cell Death in Hepatoblatoma, HepG2 Cells: Involvement of ERK1/2 MAPK

Abstract: Hesperidin, a natural flavonoid abundantly present in Citrus is known for its anti-cancer, anti-oxidant and anti-inflammatory properties. In this study we examined the effect of hesperidin on HepG2 cells. HepG2 cells treated with various concentration of hesperidin undergo a distinct type of programed cell death. Cytoplasmic vacuolization, mitochondria and endoplasmic reticulum swelling and uncondensed chromatin were observed in hesperidin treated cells. DNA electrophoresis show lack of DNA fragmentation and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
2
55
0
2
Order By: Relevance
“…Paraptosis is a form of programmed cell death described in pathologies like neurodegeneration ) that can also be induced by drugs used to treat cancer Ram & Ramakrishna 2014;Yumnam et al 2014;Zhang et al 2015). Our results reveal that follicular atresia is a complex system in which high levels of cell elimination are normal events.…”
Section: Discussionmentioning
confidence: 70%
“…Paraptosis is a form of programmed cell death described in pathologies like neurodegeneration ) that can also be induced by drugs used to treat cancer Ram & Ramakrishna 2014;Yumnam et al 2014;Zhang et al 2015). Our results reveal that follicular atresia is a complex system in which high levels of cell elimination are normal events.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, Saiprasad et al [35] showed that hesperidin can induce apoptosis through modulating BCL2/BAX levels to increase the activity of caspase-3 and caspase-9 in experimental colon cancer models. Furthermore, it has been found that hesperidin can induce cell death in hepatocellular carcinoma HepG2 cells in a caspase-independent manner by activating the ERK1/2 pathway [36]. Taken together, these results indicate that hesperidin may induce different cell death programs in different cancer cell types.…”
Section: Discussionmentioning
confidence: 77%
“…In HepG2 hepatocarcinoma cells, its ability to induce apoptosis via both mitochondrial and death receptor pathways has been demonstrated [153], as well as the non-apoptotic programmed cell death namely paraptosis [154]. Hesperidin also inhibits proliferation of Ramos Burkitt’s lymphoma cells and sensitizes them to doxorubicin-induced apoptosis through the inhibition of both constitutive and doxorubicin-mediated NF-κB activation in a PPARγ-independent manner [155].…”
Section: Preclinical Studiesmentioning
confidence: 99%